Pertukaran fasa zeolit asli ke fasa zeolit sintetik yang dicirikan oleh XRD bagi menghasilkan bahan penukar ION - Ramli, Zainab; Kamsiar, Dewi Jamaliah; Mohd. Arsat, Hasidah (The Malaysian Analytical Sciences Society (ANALIS), 2008)

(untitled)
In this study, natural mordenite was modified to other zeolites phases having low Si/Al in order to increase the cation exchange capacity of the material. Modification was carried out hydrothermally at 100oC in time range between 0 to 24 hours. The samples obtained were characterized by XRD and infrared spectroscopy. Results showed that a mixture of zeolite X and P were formed zeolite X was the dominant zeolite at 6 hrs heating time while zeolite P were dominant after 6 hrs. Ion Exchange capacity of natural mordenite, samples at 6 hr and 24 hrs heating, performed using Ca2+ cation gave cation exchange in the decreasing order of 83.57% , 72.50%, 69.45% for sample 24 hrs, 6 hrs and natural mordenite respectively. It indicates that sample having zeolite P phase is the best cation exchange capacity with 21 mg Ca2+/g zeolite with an increased of 23% capacity compared to natural zeolite.